Utilization of Fermented Water Hyacinth as an Alternative Feed to Improve the Production Performance of Muscovy Ducks - Hamiyanti, Adelina Ari; Putri, Ardyah Ramadhina Irsanti; Ciptadi, Gatot (TERNAK TROPIKA Journal of Tropical Animal Production, 2025)
Muscovy duck is a poultry commodity that has the potential to breed. In Indonesia, various types of Muscovy duck are local and imported. These types of wild ducks have different morphological characteristics. This type has more or less influenced the potential development of muscovy livestock. Entok or in Indonesia, known as Muscovy ducks, are domesticated livestock. This study aimed to evaluate the effect of fermented water hyacinth (Eichhornia crassipes) supplementation on the growth performance and body morphometric traits of Muscovy ducks (Cairina moschata). The research used 90 ducks aged four weeks, arranged in a Completely Randomized Design (CRD) with four treatments and three replications. The treatments consisted of P0 (100% commercial feed), P1 (80% commercial feed + 20% fermented water hyacinth), P2 (70% commercial feed + 30% fermented water hyacinth), and P3 (60% commercial feed + 40% fermented water hyacinth). The fermentation process involved adding 2 mL EM4 and 5% bran per kilogram of wilted water hyacinth, fermented anaerobically for 14 days. Growth data were collected weekly for eight weeks and analyzed using ANOVA at a 95% confidence level. The results showed that the addition of 30% fermented water hyacinth (P2) produced the highest final body weight (2,650 ± 58 g), average weekly gain (225.0 ± 4.8 g/week), body length (43.7 ± 1.2 cm), and chest circumference (35.5 ± 0.8 cm). Higher inclusion levels (≥40%) resulted in reduced growth performance, likely due to excessive fiber content that limited nutrient digestibility. It is concluded that fermented water hyacinth can replace up to 30% of commercial feed without negatively affecting growth, making it a sustainable, low-cost, and environmentally friendly feed alternative for Muscovy duck production.